Implementation of the Numbered Heads Together Cooperative Learning Model in Mathematics Learning for Fourth Grade Students - Sari, Dwi; Egok, Asep Sukenda; Yuneti, Armi (Global Education Journal, 2025)
Education plays an important role in developing character, improving critical thinking skills, and preparing oneself to face future challenges. This study aims to determine the completeness of mathematics learning outcomes of fourth-grade students of SD Negeri 21 Lubuklinggau. The research method used is quantitative, in the form of one group retest-posttest design. The population is all fourth-grade students of SD Negeri 21 Lubuklinggau and also the research sample of 22 students, data collection is carried out using a test technique consisting of 10 questions. The collected data are analyzed using the z-test, the average learning outcomes of the pre-test (44.98) and post-test (82.74). Based on the results of the z-test analysis, the average (x) value of the overall final test results based on the calculation is 82.74, the table is 11.070 and the count is 7.3005. Because count = 7.3005 < table = 11.070 then the data can be concluded to be normally distributed, the magnitude of z count = 4.86 and z table = 1.64 with a significance level of 5% and dk = n-1 because count = 4.86 > z table = 1.64 Ha is accepted and H0 is rejected, so it can be concluded that using the cooperative model of the Numbered Head Together type is significantly complete.